Early developmental intervention programmes post-hospital discharge to prevent motor and cognitive impairments in preterm infants - Spittle, A.; Orton, J.; Anderson, P.; Boyd, Roslyn; Doyle, L. (2012)
Background: Infants born preterm are at increased risk of developing cognitive and motor impairments compared with infants born at term. Early developmental interventions have been used in the clinical setting with the aim of improving the overall functional outcome for these infants. However, the long-term benefit of these programmes remains unclear. Objectives: To review the effectiveness of early developmental intervention post-discharge from hospital for preterm (< 37 weeks) infants on motor or cognitive development. Search methods: The Cochrane Neonatal Review group search strategy was used to identify randomised and quasi-randomised controlled trials of early developmental interventions post hospital discharge. Two review authors independently searched the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), MEDLINE Advanced, CINAHL, PsycINFO and EMBASE (1966 through to October 2012). Selection criteria: Studies included had to be randomised or quasi-randomised controlled trials of early developmental intervention programmes that began within the first 12 months of life for infants born at < 37 weeks with no major congenital abnormalities. Intervention could commence as an inpatient; however, a post-discharge component was necessary to be included in this review. The outcome measures were not pre-specified other than that they had to assess cognitive ability, motor ability or both. The rates of cerebral palsy were also documented.Data collection and analysis: Data were extracted and entered by two independent review authors. Cognitive and motor outcomes were pooled in four age groups - infancy (zero to < three years), pre-school age (three to < five years), school age (five to 17 years) and adulthood (≥ 18 years). Meta-analysis was carried out using RevMan 5.1 to determine the effects of early developmental intervention at each age range. Subgroup analysis was carried out in relation to gestational age, birthweight, brain injury, commencement of intervention and focus of intervention. Main results: Twenty-one studies met the inclusion criteria (3133 randomised patients). Only 10 of these studies were RCTs with appropriate allocation concealment. There was variability with regard to the focus and intensity of the intervention, subject characteristics and in length of follow-up. Meta-analysis concluded that intervention improved cognitive outcomes at infant age (developmental quotient (DQ): standardised mean difference (SMD) 0.31 standard deviations (SD); 95% confidence interval (CI) 0.13 to 0.50; P < 0.001; 13 studies; 2147 patients), and pre-school age (intelligence quotient (IQ); SMD 0.45 SD; 95% CI 0.34 to 0.57; P < 0.001; six studies; 1276 patients). However, this effect was not sustained at school age (IQ: SMD 0.25 SD; 95% CI -0.10 to 0.61; P = 0.16; five studies; 1242 patients). There was significant heterogeneity between studies for cognitive outcomes at infant and school ages. In regards to motor outcomes, meta-analysis of 10 studies showed a significant effect in favour of early developmental interventions; however, the effect was small (motor scale developmental quotient (DQ): SMD 0.10 SD; 95% CI 0.00 to 0.19; P = 0.04; 10 studies; 1745 patients). There was no effect on the rate of cerebral palsy in survivors; risk ratio (RR) 0.89; 95% CI 0.55 to 1.44; five studies; 737 patients).There was little evidence for a positive effect on motor outcomes in the long term, with only five of the included studies reporting outcomes at pre-school or school age. Authors' conclusions: Early intervention programmes for preterm infants have a positive influence on cognitive and motor outcomes during infancy, with the cognitive benefits persisting into pre-school age. There is a great deal of heterogeneity between studies due to the variety of early developmental intervention programmes trialled and gestational ages of the preterm infants included, which limits the comparisons of intervention programmes. Further research is needed to determine which early developmental interventions are the most effective at improving cognitive and motor outcomes, and on the longer-term effects of these programmes.